2019
DOI: 10.1002/ardp.201800227
|View full text |Cite
|
Sign up to set email alerts
|

Exploring isoxazoles and pyrrolidinones decorated with the 4,6‐dimethoxy‐1,3,5‐triazine unit as human farnesyltransferase inhibitors

Abstract: Unprecedented triazinyl‐isoxazoles were afforded via an effective cycloaddition reaction between nitrile oxides and the scarcely described 2‐ethynyl‐4,6‐dimethoxy‐1,3,5‐triazine as dipolarophile. The biological evaluation of the newly synthesized compounds showed that the inhibition of human farnesyltransferase by zinc complexation could be improved with triazine‐isoxazole moieties. The replacement of the isoxazole unit by a pyrrolidin‐2‐one was detrimental to the inhibitory activity while the pyrrolidin‐2‐thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As analogues of isoxazole compounds, in 2019 Lucescu et al [ 78 ] synthesized and tested triazine-pyrrolidine-2-thiones 112a,b (Fig. 23 ) on the human protein farnesyltransferase (FTase).…”
Section: Pyrrolidine Derivatives From Commercial Building Blocksmentioning
confidence: 99%
“…As analogues of isoxazole compounds, in 2019 Lucescu et al [ 78 ] synthesized and tested triazine-pyrrolidine-2-thiones 112a,b (Fig. 23 ) on the human protein farnesyltransferase (FTase).…”
Section: Pyrrolidine Derivatives From Commercial Building Blocksmentioning
confidence: 99%
“…The preliminary results showed that meta and para positions of phenyl substituents are effective for antitumor activity (Table 1), in particular, if these positions were occupied by halo substituents 3b,c (entries: 2, 3). These results directed us to synthesize a series of unreported pyrrolidines (entries: [5][6][7][8][9][10][11] and pyrroles (entries: 12-14).…”
Section: Chemistrymentioning
confidence: 99%
“…[1] Therefore, newer approaches to treat cancer and explorations on the mechanism of cancer growth are in continuous demand. [2,3] Recently, the development of novel anticancer drugs has mainly focused on molecularly targeted therapeutics, [4,5] but the conventional approach [6][7][8][9] based on screening of cytotoxic agents in multiple human tumor cell lines remains the most successful method.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the obtained isoxazole 27 was confirmed by X-ray structure analyses and the electronic structure was elucidated by computational methods (Scheme 14) [16]. Lucescu and co-workers [9] conducted the cycloaddition reaction between the scarcely described 2-ethynyl-4,6-dimethoxy-1,3,5-triazine (28) as dipolarophile and the 9-anthradehyde oxime in the presence of NCS, potassium bicarbonate in ethyl acetate as solvent (Scheme 15). The product, 2-[3-(9-anthryl)isoxazol-5-yl]-4,6-dimethoxy-1,3,5-triazine (29), was obtained in 64% yield.…”
Section: Synthesis Of Isoxazolesmentioning
confidence: 93%
“…Higher yields (up to 90%) were obtained by using Na-Zn 5 W 19 as the catalyst in water as solvent (Scheme 3). However, the best method to prepare the desired oxime 2 remains the classical addition of hydroxylamine to the aldehyde 4 in hydro-alcoholic solution affording the oxime with yields in the range 95-99% [9,10]. We conclude this introductive part dedicated to the synthesis of the anthraldehyde oxime citing an example of a 10-substituted derivative.…”
Section: Introductionmentioning
confidence: 99%